2017
DOI: 10.1038/nrcardio.2017.76
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in cardiovascular disease

Abstract: Cardiovascular disease (CVD) follows a seasonal pattern in many populations. Broadly defined winter peaks and clusters of all subtypes of CVD after 'cold snaps' are consistently described, with corollary peaks linked to heat waves. Individuals living in milder climates might be more vulnerable to seasonality. Although seasonal variation in CVD is largely driven by predictable changes in weather conditions, a complex interaction between ambient environmental conditions and the individual is evident. Behavioural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
172
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(219 citation statements)
references
References 156 publications
11
172
1
4
Order By: Relevance
“…A vaccination strategy can reduce hospital admissions [21, 23] and may improve heart failure prognosis [21]. Our data are consistent with previous findings [3, 5], and the peak of mortality due to refractory heart failure observed in the cold months can be explained, partially, by the rise in viral infections, including influenza.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…A vaccination strategy can reduce hospital admissions [21, 23] and may improve heart failure prognosis [21]. Our data are consistent with previous findings [3, 5], and the peak of mortality due to refractory heart failure observed in the cold months can be explained, partially, by the rise in viral infections, including influenza.…”
Section: Discussionsupporting
confidence: 82%
“…The proposed explanation for this is that socioeconomic conditions, or the ability to protect oneself from the cold (by means of home insulation or appropriate outerwear), and other less clearly defined factors, also play an important role in seasonality [19, 20]. Poor regions are more vulnerable to seasonal threats [3]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that onset of STEMI has a circadian rhythm with a peak during diurnal hours has been well described 4, 5, 6, 7, 8, 9, 10, 11, 12. A seasonal pattern13 in the occurrence of STEMI was also found with a salient peak of cases in the winter months and a marked nadir of cases in the summer months 14, 15, 16, 17, 18, 19. Several studies have investigated the reason behind the winter peak and suggested that STEMI is more common in winter and more common on colder days, independent of season 20, 21.…”
Section: Introductionmentioning
confidence: 99%